Astrocytic Connexin43 Channels as Candidate Targets in Epilepsy Treatment - Walrave, Laura (Biomolecules, 2020)
In epilepsy research, emphasis is put on exploring non-neuronal targets such as astrocytic proteins, since many patients remain pharmacoresistant to current treatments, which almost all target neuronal mechanisms. This paper reviews available data on astrocytic connexin43 (Cx43) signaling in seizures and epilepsy. Cx43 is a widely expressed transmembrane protein and the constituent of gap junctions (GJs) and hemichannels (HCs), allowing intercellular and extracellular communication, respectively. A plethora of research papers show altered Cx43 mRNA levels, protein expression, phosphorylation state, distribution and/or functional coupling in human epileptic tissue and experimental models. Human Cx43 mutations are linked to seizures as well, as 30% of patients with oculodentodigital dysplasia (ODDD), a rare genetic condition caused by mutations in the GJA1 gene coding for Cx43 protein, exhibit neurological symptoms including seizures. Cx30/Cx43 double knock-out mice show increased susceptibility to evoked epileptiform events in brain slices due to impaired GJ-mediated redistribution of K(+) and glutamate and display a higher frequency of spontaneous generalized chronic seizures in an epilepsy model. Contradictory, Cx30/Cx43 GJs can traffic nutrients to high-energy demanding neurons and initiate astrocytic Ca(2+) waves and hyper synchronization, thereby supporting proconvulsant effects. The general connexin channel blocker carbenoxolone and blockers from the fenamate family diminish epileptiform activity in vitro and improve seizure outcome in vivo. In addition, interventions with more selective peptide inhibitors of HCs display anticonvulsant actions. To conclude, further studies aiming to disentangle distinct roles of HCs and GJs are necessary and tools specifically targeting Cx43 HCs may facilitate the search for novel epilepsy treatments.